1996
DOI: 10.1073/pnas.93.1.274
|View full text |Cite
|
Sign up to set email alerts
|

Early p53 alterations in mouse skin carcinogenesis by UVB radiation: immunohistochemical detection of mutant p53 protein in clusters of preneoplastic epidermal cells.

Abstract: High levels of the p53 protein are immunohistochemically detectable in a majority of human nonmelanoma skin cancers and UVB-induced murine skin tumors. These increased protein levels are often associated with mutations in the conserved domains of the p53 gene. To investigate the timing of the p53 alterations in the process of UVB carcinogenesis, we used a well defined murine model (SKH:HR1 hairless mice) in (1), and from animal studies it appeared that the UVB part of the solar spectrum is the most carcinog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
164
1
4

Year Published

1997
1997
2005
2005

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 195 publications
(176 citation statements)
references
References 19 publications
7
164
1
4
Order By: Relevance
“…In hairless mouse skin, UV-induced p53 mutations could be detected by AS-PCR as early as 1 week after the first UV radiation exposure, with 80-90% of animals incurring p53 mutations after 8 weeks of UV treatment (Ouhtit et al, 2000a). Clones of keratinocytes carrying mutant p53 have also been detected in mouse skin within 2-3 weeks after UV treatment (Berg et al, 1996;Rebel et al, 2001;Remenyik et al, 2003). In this study, we investigated the fate of p53 mutations and the development of skin cancer after discontinuation of UV treatment.…”
Section: Discussionmentioning
confidence: 86%
See 4 more Smart Citations
“…In hairless mouse skin, UV-induced p53 mutations could be detected by AS-PCR as early as 1 week after the first UV radiation exposure, with 80-90% of animals incurring p53 mutations after 8 weeks of UV treatment (Ouhtit et al, 2000a). Clones of keratinocytes carrying mutant p53 have also been detected in mouse skin within 2-3 weeks after UV treatment (Berg et al, 1996;Rebel et al, 2001;Remenyik et al, 2003). In this study, we investigated the fate of p53 mutations and the development of skin cancer after discontinuation of UV treatment.…”
Section: Discussionmentioning
confidence: 86%
“…This acute regression phase may be followed by a significantly slower second phase (Berg et al, 1996). Berg et al (1996) found that more than 50% of p53-positive patches induced in Skhhr1 mouse skin by exposure to 39 kJ/m 2 of total UV radiation over a period of 30 days disappeared within the first 2 weeks after discontinuation of UV irradiation. The rate of disappearance of p53-positive patches was significantly higher (85%) when the total dose of UV radiation was decreased to 22 kJ/m 2 (Berg et al, 1996).…”
Section: ) Previous Studies Havementioning
confidence: 99%
See 3 more Smart Citations